Solution of macromodels with Hansen-Sargent robust policies: Summary and some extensions - Paolo Giordani; Paul Söderlind (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
We summarize some methods useful in formulating and solving Hansen-Sargent robust control problems, and suggest extensions to discretion and simple rules. Matlab, Octave, and Gauss software is provided. We illustrate these extensions with applications to the term structure of interest rates, the time inconsistency of optimal monetary policy, the effects of expectations on the variances of inflation and output, and on whether central banks should make their forecasts public.
Keywords: E43; E52; L61; 330; robustness; model uncertainty; discretion; simple rules; Prognoseverfahren; Kontrolltheorie; Theorie